Ultrabroadband Plasmonic Absorber for Terahertz Waves. Issue 3 (28th October 2014) - Cheng, Yong Zhi; Withayachumnankul, Withawat; Upadhyay, Aditi; Headland, Daniel; Nie, Yan; Gong, Rong Zhou; Bhaskaran, Madhu; Sriram, Sharath; Abbott, Derek
<x xml:space="preserve">Abstract</x> Perfect absorbers that exhibit broadband absorption of terahertz radiation are promising for applications in imaging and detection due to enhanced contrast and sensitivity in this relatively untapped frequency regime. Here, terahertz plasmonics is used to demonstrate near‐unity absorption across a broad spectral range. The absorber comprises a planar array of cross‐shaped structures defined by surface etching of doped silicon. Absorbance of over 90% is observed numerically with a relative bandwidth of 90% from 0.67 to 1.78 THz, in reasonable agreement with experimental observation. This ultrabroadband absorption is attributed to two resonance modes supported by plasmonic cavities that are defined by the etched cross structure. This terahertz absorber is single‐layered, polarization‐insensitive, and exhibits consistent performance across a wide range of incidence angles. The plasmonic‐based approach for enhancing absorption is a potential precursor to the realization of efficient bolometric imaging and communications at terahertz frequencies.